Financial incentives to work for disability insurance recipients: Sweden's special rules for continuous deduction - Josefine Andersson (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2018)
Evidence from around the world suggests that individuals who are awarded disability benefits in some cases still have residual working capacity, while disability insurance systems typically involve strong disincentives for benefit recipients to work. Some countries have introduced policies to incentivize disability insurance recipients to use their residual working capacities on the labor market. One such policy is the continuous deduction program in Sweden, introduced in 2009. In this study, I investigate whether the financial incentives provided by this program induce disability insurance recipients to increase their labor supply or education level. Retroactively determined eligibility to the program with respect to time of benefit award provides a setting resembling a natural experiment, which could be used to estimate the effects of the program using a regression discontinuity design. However, a simultaneous regime change of disability insurance eligibility causes covariate differences between treated and controls, which I adjust for using a matching strategy. My results suggest that the financial incentives provided by the program have not had any effect on labor supply or educational attainment.
Keywords: H53; H55; I18; J22; 330; disability insurance; financial incentives; continuous deduction; regression discontinuity design; propensity score matching; nearest neighbor matching